ANALISIS SISTEM PENGENDALIAN INTERNAL KAS PADA BANK : Studi Kasus pada Bank Tabungan Negara (BTN) Kota Serang - Azhari, Ratu Syahna; Fadilah, Jamilatul; Aguspriyani, Yani (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Cash represents a valuable asset crucial for the seamless functioning of banking operations. Conversely, the effectiveness of internal control systems significantly influences the operational management of banking activities, particularly in handling cash. A breakdown in the internal control system could disrupt banking activities and adversely impact overall banking performance. This study aims to investigate the Controlling Internal System within the Indonesian banking sector, with a focus on the Tabungan Negara Bank (BTN).